2021
DOI: 10.1177/11297298211000871
|View full text |Cite
|
Sign up to set email alerts
|

When the course deviates from expected: Misplacement of an epicutaneo-caval catheter in a neonate

Abstract: Central venous access, a common and essential component of the care of the critically ill neonate, is associated with complications such as infection, thrombosis, and bleeding. Unintentional arterial cannulation of a venous catheter is a rare but potentially dangerous complication. In the report, we describe the accidental cannulation of an artery with an epicutaneo-caval catheter in an extremely low birth weight infant. We discuss the physical and radiological findings that raise the suspicion of an arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Considering that the younger the gestational age and the lower the birth weight, the lower the autoimmunity and the worse the barrier function of skin and mucosa. [21] The greater the chance of CRBSI. Some scholars prospectively studied the risk factors of nosocomial infection in neonates in ICU, and the results showed that birth weight <1 kg was the largest risk factor of nosocomial infection in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the younger the gestational age and the lower the birth weight, the lower the autoimmunity and the worse the barrier function of skin and mucosa. [21] The greater the chance of CRBSI. Some scholars prospectively studied the risk factors of nosocomial infection in neonates in ICU, and the results showed that birth weight <1 kg was the largest risk factor of nosocomial infection in neonates.…”
Section: Discussionmentioning
confidence: 99%